2016
DOI: 10.1186/s12890-016-0294-1
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin attenuates bleomycin-induced pulmonary fibrosis via adenosine A2a receptor related TGF-β1-induced ERK1/2 signaling pathway

Abstract: BackgroundBaicalin has been reported to have anti-fibrosis effect; however, its mechanism still remains to be elucidated. Adenosine A2a receptor (A2aR) is a novel inflammation regulator, and transforming growth factor-β1 (TGF-β1)-induced extracellular signal regulated kinase1/2 (ERK1/2) signaling pathway plays an important role in idiopathic pulmonary fibrosis (IPF). This study was to explore the relationship of A2aR and TGF-β1-induced ERK1/2 in bleomycin (BLM)-induced pulmonary fibrosis in mice, and to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 43 publications
(41 reference statements)
6
34
0
Order By: Relevance
“…Also, Baicalin has an anti-fibrosis effect on bleomycin-induced pulmonary fibrosis [26]. Similar phenomena were also observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…Also, Baicalin has an anti-fibrosis effect on bleomycin-induced pulmonary fibrosis [26]. Similar phenomena were also observed in our study.…”
Section: Discussionsupporting
confidence: 91%
“…at maximum solubility in DMSO in this proof-of-principle experiment. The applied dosage of Baicalein is well established as it has been used in previously described animal studies [ 73 , 74 ], and preliminary dosage finding experiments of our study group showed no significant impact at lower concentrations. Previous studies regarding the protective effects of DMSO on hepatic ischemia and reperfusion used significantly lower dosages (500 mg/kg b.w.…”
Section: Discussionmentioning
confidence: 62%
“…Inhibits CD8 + CTL and Th1 expansion to alloantigens. [ 110 ] 27 CD4 + T cells Inhibits TCR-mediated IFN-γ release [ 111 ] 28 CD4 + CD25 + FoxP3 + Tregs Increases number of Tregs and increases the expression of CTLA-4 receptor [ 112 ] 29 CD4 + CD25 + FoxP3 + Tregs Upregulates ecto-enzymes CD39 and CD73 expression accelerating adenosine generation from extracellular ATP [ 112 ] 30 AdoRA2A knockout mice Bleomycin-induced fibrosis is more severe and elevated TGF-β1 is higher than in wild-type mice [ 113 ] 31 AdoRA2A and AdorA2B Adenosine Macrophages Differentiation of monocytes towards M2 macrophages with VEGF and IL-10 release [ 114 118 ] 32 Macrophages Inhibits LPS-induced IL-6, MIP-2 and TNF-α release [ 119 , 120 ] 33 AdoRA2B Adenosine Neutrophils Inhibits neutrophil recruitment and transmigration, release of TNF-α, IL-6, MIF-1α and IL-8 [ 121 , 122 ] 34 Neutrophils Inhibits superoxide generation [ 123 ] 35 Neutrophils Inhibits TNF-α release [ 76 ] 36 Macrophages Stimulates IL-10 release [ 124 ] 37 …”
Section: Prolonged Induced Excess Of Purinergic Signalling Leads To Pmentioning
confidence: 99%